KESETARAAN GENDER DALAM ISLAM DI UNIVERSITAS PENDIDIKAN INDONESIA - Diyana Maliha Fauziyyah; Hanifah Nurul Q; Putra Yudha; Usup Romli (PSIKOWIPA (Psikologi Wijaya Putra), 2022)
This study was conducted to determine the understanding of gender in Islam. The study used a quantitative design method by distributing a questionnaire in the form of a google form to students at the University of Indonesia Education to obtain the necessary data. The sample in this study were active students at the Indonesian Education University and were Muslim. The data collection technique in this research is a questionnaire (questionnaire). The result of this study is that the average respondent already knows in general about gender, but has not studied much in terms of the Qur'an and Hadith.